Micropropagation and Evaluation of Genetic Stability of Wild Curcuma Species and C. longa Morphotypes Using Random Amplified Polymorphic DNA - Thaliyangal, Yusuf Akkara and Rajeshkumar (Current Botany, 2015)
Species specific responses in micropropagation of 10 wild species of Curcuma and 15 morphotypes of C. longa were observed. Five to eight shoots were produced from a single rhizome bud explant of C. aeruginosa, C. amada, C. amarissima and six morphotypes of C. longa (M1, M4, M7,M9,M14 and M16) in Murashige and Skoog (MS) medium containing 5.0 mg dm-3 6-Benzyl Adenine (BA). C. aurantiaca, C. caesia, C. zeodaria and four C. longa morphotypes (M2, M8, M10 and M11) produced six to eleven shoots in MS medium containing 0.1 mg dm-3 Indole-3 acetic acid (IAA) and 2.5 mg dm-3 BA. C. brog, C. latifolia, C. malabarica, C. raktakanta and five C. longa morphotypes (M3, M15, M17, M18 and M19) developed five to seven shoots in MS medium containing 0.1 mg dm-3 IAA and 5.0 mg dm-3 BA. Initiated shoots were multiplied and rooted in the same medium. Rooted plantlets were transferred to field and 95% of the plantlets survived during acclimatisation. Genetic stability of in- vitro raised plants was tested using 30 Random Amplified Polymorphic DNA (RAPD) primers during each stage of subculture. Twenty primers produced 275 bands out of which 249 were polymorphic exhibiting 90.53% polymorphism for the species and morphotypes establishing their wide genetic basis. In-vitro cultures were stable in their genetic makeup until fifth or sixth passage of subculture depending on the species and showed variation in RAPD banding pattern after these cycles. These results indicates that exposure to long term in-vitro conditions resulted in variation in the DNA in almost all the species and morphotypes of Curcuma.